A Comprehensive Investigation on Development of Lightweight Aluminium Miniature Gears by Thermoelectric Erosion Machining Process - Sujeet Kumar Chaubey; Neelesh Kumar Jain; Kapil Gupta (Micromachines, 2021)
Nowadays, size, weight, and durability are crucial factors in product development that draw the attention of many researchers and engineers towards research and innovation in the micromanufacturing area. This paper reports on the development of a lightweight aluminium gear of miniature size with a bore and hub using wire-assisted thermoelectric erosion machining (WTEM). The external spur gear was cut from 7075 aluminium alloy round stepped gear blank by WTEM using 0.25 mm brass wire. Further, the miniature gear was tested for various manufacturing quality parameters such as microgeometry, surface roughness, and microstructure, along with evaluating process productivity in terms of volumetric gear cutting speed To understand the mechanism of development of aluminium miniature gear, an investigation on the influence of WTEM parameters namely servo-voltage, pulse-on time, pulse-off time, and wire speed on surface roughness was conducted. A total of 18 gears were fabricated following Taguchi L9 (34) orthogonal array approach of design of experiments considering the randomization and replication. A typical average surface roughness value of 1.58 μm and manufacturing quality of DIN standard number 7 based on gear microgeometry were successfully achieved. Microscopic investigation revealed uniform and accurate tooth profiles, flank surfaces free from burrs and contaminants, and uniform microstructure that confirm the good performance characteristics of the developed lightweight miniature gear of aluminium. This investigation will add new results in the field as regards the development of lightweight microparts.